Penerapan Metode Discovery Learning Untuk Meningkatkan Aktivitas Belajar dan Hasil Belajar Siswa Kelas XI IPS 1 MA Muallimin NW Pancor 2018/2019 - Farhana Muhammad; Hannah Hupiah (Universitas Hamzanwadi, 2018)
This study aims to determine whether the Discovery Learning model can improve learning activities and can improve the learning outcomes of XI IPS1 students at the MA Muallimin NW Pancor.This study uses a Classroom Action Research. This study seeks to improve the quality of learning activities and learning outcomes in a class based on the problems found by using new actions applied by researchers. The subjects in this study were students of class XI IPS1 MA Muallimin Pancor TA2018/2019 with 30 students. In this study there are three cycles, which start from planning, implementation and evaluation.The results of this class action research are: The method of discovery learning can improve the learning activities of students of class XI IPS1 MA Muallimat NW Pancor academic year 2018/2019. The results showed that after the application of the discovery learning model the average learning activity of students had increased. In the first cycle the average learning activity was 8.53 with a less active category, in the second cycle it increased to 11.00 with a fairly active category. In the third cycle it increased to 13.70 with a fairly active category. Discovery learning model can improve learning outcomes of students of class XI IPS1 MA Muallimin NW Pancor academic year 2018/2019. The results showed that after the implementation of the discovery learning model the average student learning outcomes had increased. In the first cycle the average learning outcomes were 61.33 with sufficient categories, in the second cycle it increased to 65.67 in the good category. In the third cycle it increased to 74.00 in the good category